2021
DOI: 10.1111/resp.14016
|View full text |Cite
|
Sign up to set email alerts
|

Cone‐beam computed tomography versus computed tomography‐guided ultrathin bronchoscopic diagnosis for peripheral pulmonary lesions: A propensity score‐matched analysis

Abstract: Diagnostic yields of CT‐guided and CBCT‐guided transbronchial biopsy for peripheral pulmonary nodules were compared by propensity score‐matched analysis. Overall diagnostic yields were 47.9% for CT‐guided biopsy and 72.9% for CBCT‐guided biopsy. CBCT‐guided biopsy improved the diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…Other CBCT-NB literature report a wide range of diagnostic accuracies. Reported diagnostic accuracies in the range of 70%, such as Kawakita et al (72.9%),31 Casal et al (70%)32 and our own cohort when including the learning curve (76.4%13) would not be cost-effective when compared with TTNB in our model. Other centres have, however, reported higher outcomes, with Ali et al 33 reporting a diagnostic accuracy of 90% and Pritchett et al 83.7% 11.…”
Section: Discussionmentioning
confidence: 73%
“…Other CBCT-NB literature report a wide range of diagnostic accuracies. Reported diagnostic accuracies in the range of 70%, such as Kawakita et al (72.9%),31 Casal et al (70%)32 and our own cohort when including the learning curve (76.4%13) would not be cost-effective when compared with TTNB in our model. Other centres have, however, reported higher outcomes, with Ali et al 33 reporting a diagnostic accuracy of 90% and Pritchett et al 83.7% 11.…”
Section: Discussionmentioning
confidence: 73%
“…The recent development of 1.7 mm channel size allows the passage of r-EBUS [28], which provides a 360° view of the surrounding lesion by the ultrasound transducer [43] and shows a pooled diagnostic yield of 0.73 (95% CI, 0.70-0.76) [40]. The r-EBUS probe position relative to the lesion was known to be associated with the diagnostic yield of TBB, where the diagnostic yield of within, adjacent to, and outside the lesion was Shinagawa 2004 [24] Yamamoto 2004 [25] Shinagawa 2007 [26] Tachihara 2007 [27] Oki 2009 [28] Matsuno 2011 [22] Oki 2012 [29] Asano 2013 [30] Oki 2015 [31] Franzen 2016 [32] Tokoro 2016 [33] Ali 2019 [34] Diez-Ferrer 2019 [35] Oki 2019 [13] Sehgal 2019 [36] Sumi 2020 [37] Kawakita 2021 [38] Sumi 2021 [39] Zheng 2021 [23] Total (95% CI) 0.83, 0.61, and 0.04, respectively (p < 0.001) [44]. In line with this, Nishi et al [45] reported that UTB showed improved r-EBUS probe position for PPL after substituting thin bronchoscope (adjacent, 12; not visible, 32) by UTB (within, 26; adjacent, 11; not visible, 7) combined with fluoroscopy and VBN.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT employs a flexible C‐arm that scans images in a cone shape rather than the traditional fan shape, providing 3D images with 200–300 times less radiation than conventional CT. In a study comparing ultrathin bronchoscopy with VBN using CBCT versus CT guidance, the diagnostic yield was 72.9% versus 47.9%, respectively 63 . In a prospective cross‐over study comparing primary guidance modalities of CBCT and EMN, navigation success was 89.9% when the two modalities were combined.…”
Section: Interventional Pulmonologymentioning
confidence: 99%
“…In a study comparing ultrathin bronchoscopy with VBN using CBCT versus CT guidance, the diagnostic yield was 72.9% versus 47.9%, respectively. 63 In a prospective cross-over study comparing primary guidance modalities of CBCT and EMN, navigation success was 89.9% when the two modalities were combined. However, overall diagnostic accuracy remained lower than navigation success at 72.4%.…”
Section: Fluoroscopic Navigation and Cbctmentioning
confidence: 99%